European community regulation framework for electronic commerce - Lopez-Tarruella, Aurelio (2001)
Explains the basic principles for the establishment of the freedom to provide Information Society Services. Deals with some other legal questions which may crop up in the different steps of the service provider's economic activity viz. promotion of products and services; electronic contracts; liability of intermediary service providers; and law inforcement mechanisms. Examines the external dimension of the European Union's Information Society policy.